Tradisi Arab Sebagai Asbab Nuzul: Analisis terhadap Pembatalan Nasab Ayah Angkat terhadap Anak Angkat dalam Surah Al-Ahzab Ayat 5 Menurut Tafsir Al-Qur’an - Sumantri Adenin (STAIN Bengkalis, 2021)
One of the traditions that flourished since the Jahiliah era is the child's lifting. The same status as a child. Until the episode is changed, it is no longer his biological parents. This article aims to see how the activity of the advisors conducted on other than the biological father is very influential in the survival of the nation's children, both against the inheritance law, the law of guardians, etc. Some interpretations that some of the legal consequences resulting from the adoption of a child are as follows: First, the transfer of maintenance responsibilities for his daily life, the cost of education and so on from the biological parent to his adoptive parents. Second, the adoption of the child does not sever blood relations or nasab with the biological parents and their families, so that between them remains a mahram relationship and an inherited relationship. Third, the adoption of the child does not cause blood relations or nasab between the adopted child and his adoptive parents, so that between them there is no mahrom relationship and inherited relationship. Fourth, Between the adopted child and his biological father remains a mahrom relationship and an inherited relationship.